Uncovering evapotranspiration patterns in the Murray Darling Basin over two decades - Amirhossein Shadmehri Toosi; Okke Batelaan; Margaret Shanafield; Huade Guan (Journal of Hydrology: Regional Studies, 2025)
Study Region: The Murray Darling Basin (MDB), Australia. Study Focus: Actual evapotranspiration (AET) plays a critical role in the basin's water balance, influencing water availability for irrigation and other uses. Understanding the dynamics of AET in the MDB under changing land cover and climate is essential for ensuring the long-term sustainability of the region's economy and ecosystem. We do this utilising high-resolution land cover data in conjunction with MODIS and CMRSET AET datasets at the MDB and sub-catchments scale from 2001 to 2020. New Hydrological Insights for the Region: A strongly decreasing east-west AET gradient is observed in both MODIS and CMRSET and is aligned closely with rainfall (P) patterns. CMRSET patterns demonstrated a stronger correlation and are more realistic, while MODIS underestimates AET. AET follows the order Natural Terrestrial Vegetation (NTV) > Cultivated Terrestrial Vegetation (CTV) > Natural Bare Surface (NS), but P acts as the main driver of AET variability. AET/P shows greater spatial variability in arid regions, driven by episodic rainfall and ephemeral vegetation responses. However, a statistical absence of differences in AET and AET/P between land covers for some catchments indicates important confounding factors. Instances of AET/P > 1 reflect the use of supplementary water sources and moisture carryover from previous wet years, indicating the resilience of different landscapes to drought.